Towards the development of sustainable hydro energy in Lithuania - Jatautas, Jaunius; Mierauskas, Pranas (International Conference “Environmental Engineering”, 2017)
Development of renewable energy sources together with sustainable development covers a complicated range of issues which require complex assessment in the context of Lithuania’s energy independence. Hydropower is an integral part of renewable energy resources and affects both the natural environment and human society. Although negative impact of hydropower on the environment is acknowledged, advances in modern technology can reduce the potential damage, especially when developing a network of small hydropower plants in Lithuania. Moreover, simple mentation and continuity of this kind of projects enables to improve the economic and social situation, e.g. by creating new jobs. Construction of small hydropower plants in combination with a sustainable development strategy would help to avoid the possible damage to the natural environment and would contribute to improvement of the country’s economic and social landscape. Limitation of the negative impact on the environment is primarily based on techno logical solutions – the appropriate construction of fish ladders or other passes at dams enables fish migration. Mean while, contribution to improvement of the economic and social situation in the case of small hydropower plants de pends on political decisions and activity of lobby groups.